The physiology of learning and memory: Role of peptides and stress - YEGEN, BERRAK; GÜLPINAR, MEHMET ALİ (BENTHAM SCIENCE PUBL LTD, 2004)
The neuropeptides, as well as their respective receptors, are widely distributed throughout the mammalian central nervous system. During learning and memory processes, besides structural synaptic remodeling, changes are observed at molecular and metabolic levels with the alterations in neurotransmitter and neuropeptide synthesis and release. While there is consensus that brain cholinergic neurotransmission plays a critical role in the processes related to learning and memory, it is also well known that these functions are influenced by a tremendous number of neuropeptides and non-peptide molecules. Arginine vasopressin (AVP), oxytocin, angiotensin II, insulin, growth factors, serotonin (5-HT), melanin concentrating hormone, histamine, bombesin and gastrin-re leasing peptide (GRP), glucagon-like peptide-1 (GLP-1). cholecystokinin (CCK), dopamine, corticotropin releasing factor (CRT) have modulatory effects on learning and memory. Among these peptides CCK, 5-HT and CRF play strategic roles in the modulation of memory processes under stressful conditions. CRF is accepted as the main neuropeptide involved in both physical and emotional stress.. with a protective role during stress, possibly through the activation of the hypothalamo-pitiuitary (HPA) axis. The peptide CCK has been proposed to facilitate memory processing and CCK-like immunoreactivity in the hypothalamus was observed upon stress exposure, suggesting that CCK may participate in the central control of stress response and stress-induced memory dysfunction. On the other hand, 5-HT appears to play a role in behaviors that involve a high cognitive demand and stress exposure activates serotonergic systems in a variety of brain regions. The physiological role and therapeutic efficacy of various neuropeptides and the impact of stress exposure in the acquisition and consolidation of memory will be reviewed thoroughly.
Keywords: Alzheimer's disease (AD); acquisition; consolidation; stress; social memory; serotonin (5-HT); cholecystokinin (CCK); corticotropin releasing factor (CRF); hypothalomo-pitiutary (HPA) axis; CORTICOTROPIN-RELEASING-FACTOR; CELL-ADHESION MOLECULE; LONG-TERM POTENTIATION; NITRIC-OXIDE SYNTHASE; PASSIVE-AVOIDANCE TASK; MORRIS WATER MAZE; FACTOR (CRF)-LIKE IMMUNOREACTIVITY; HIPPOCAMPAL CA3C NEURONS; CHRONIC RESTRAINT STRESS; CENTRAL 5-HT4 RECEPTORS